Employment Models of Platform Companies in Norway: A Distinctive Approach? - Jesnes, Kristin (Nordic Journal of Working Life Studies, 2019)
The past decade has seen an increase in ‘platform companies’ functioning as the intermediary between workers and customers.The way these companies structure the labour process has significant implications for working conditions. In this article, we ask: In what ways does platform work in Norway differ from standard employment relationships? And do different employment strategies of platform companies put workers in precarious situations? The article builds on qualitative interviews with CEOs of platform companies in Norway, and aims to contribute to the literature by formulating a typology of the employment models of platform companies emerging in the Nordic countries. The platforms’ employment models are compared to the standard employment relationship and precariousness. Finally, the article suggests that institutions matter for why some platform companies adopt elements of the standard employment relationships as they appear in the Nordic labour market models, and discusses the implications of this.